Environmental Accounting and Corporate Social Responsibility in Realizing the Sustainable Development Goals - Siti Kustinah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
A descriptive examination of the use of national environmental accounting in Indonesia and its relationship to the corporate social responsibility process, which helps to the fulfillment of sustainable development objectives, is the purpose of this article. To develop the research, we employ descriptive-level research. The type of literature research between the main results of this work is an overview with regulations related to environmental protection and components of the Indonesian Institute of Accountants Financial Accounting System, as well as progress in the categorization and approval of indicators related to environmental protection in each of the sustainable development goals. It is concluded that the implementation and enforcement of indicators for sustainable development goals has required significant effort on the part of the specific institutions in each country; for statistical information on environmental aspects, to put into effect the best decisions made by the government and its agencies, and to implement the best decisions made by the government and its agencies.